Consideration of nutrition and sustainability in public definitions of 'healthy' food: an analysis of submissions to the US FDA - Emily H Belarmino; Michelle Carfagno; Lauren Kam; Kene-Chukwu Ifeagwu; Miriam E Nelson; Rebecca A Seguin-Fowler (Cambridge University Press, 2024)
Abstract Objective: To better understand how the public defines 'healthy' foods and to determine whether the public considers sustainability, implicitly and explicitly, in the context of healthy eating. Design: We conducted a content analysis of public comments submitted to the US FDA in 2016 and 2017 in response to an invitation for feedback on use of the term 'healthy' on food labels. The analysis explored the ways in which commenters' definitions of 'healthy' aligned with the 2015-2020 Dietary Guidelines for Americans and whether their definitions considered sustainability. Setting: The US Government's Regulations.gov website. Participants: All 1125 unique comments from individuals and organisations. Results: Commenters' definitions of 'healthy' generally mirrored the recommendations that the Dietary Guidelines for Americans put forth to promote a 'healthy eating pattern'. Commenters emphasised the healthfulness of fruit, vegetables, whole grains, fish and other minimally processed foods and the need to limit added sugars, sodium, saturated and trans fats and other ingredients sometimes added during processing. One-third of comments (n 374) incorporated at least one dimension of sustainability, mainly the environmental dimension. Commenters who mentioned environmental considerations primarily expressed concerns about synthetic chemicals and genetic modification. Less than 20 % of comments discussed social or economic dimensions of sustainability, and less than 3 % of comments (n 30) used the word 'sustainability' explicitly. Conclusions: This novel analysis provides new information about the public's perceptions of 'healthy' foods relative to nutrition and sustainability considerations. The findings can be used to advance policy discussions regarding nutrition labelling and guidance.